2010
DOI: 10.1111/j.1440-1754.2009.01657.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features at the onset of childhood type 1 diabetes mellitus in Shenyang, China

Abstract: The duration between the onset of the symptoms and diagnosis was long, and the proportion of DKA in children with newly diagnosed diabetes mellitus was high. These findings call for a collaborative effort for the early recognition of symptoms by patients and physicians in order to avoid more severe types of presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
17
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 15 publications
7
17
0
Order By: Relevance
“…The age-related incidence in our series was 54.4% in school-aged children (6-13 years), followed by 23.2% in infants (< 2 years), and 22.2% in toddlers (2-6 years), revealing a higher incidence of T1DM in the older age group and rise of the incidence among younger groups, accounting for 45.5% of patients below 6 years of age. This is in agreement with the findings of Al-Magamsi and Habib [8], Mayer-Davis et al [9], and Xin et al [10], who reported a higher incidence in the age group 5-9 years and 10-14 years and a Frequency of misdiagnosis and mismanagement among the studied group (97 children).…”
Section: Discussionsupporting
confidence: 93%
“…The age-related incidence in our series was 54.4% in school-aged children (6-13 years), followed by 23.2% in infants (< 2 years), and 22.2% in toddlers (2-6 years), revealing a higher incidence of T1DM in the older age group and rise of the incidence among younger groups, accounting for 45.5% of patients below 6 years of age. This is in agreement with the findings of Al-Magamsi and Habib [8], Mayer-Davis et al [9], and Xin et al [10], who reported a higher incidence in the age group 5-9 years and 10-14 years and a Frequency of misdiagnosis and mismanagement among the studied group (97 children).…”
Section: Discussionsupporting
confidence: 93%
“…Similar results were observed in the study by Bober et al where they declared that a history of infection or febrile illness could increase the risk of DKA more than six-times (24). Such results were repeated by Xin et al and they found a febrile illness history that elevated DKA risk about two folds (25). Fever in children with DM1 might be a consequence of an infection which could cause insulin resistance by itself through cytokine release and deteriorate the metabolic condition and lead to DKA.…”
Section: Discussionsupporting
confidence: 77%
“…with newly diagnosed T1DM. 15 We noted difference in gender distribution between younger and older age groups. There was female predominance in older (10 -15 yrs.)…”
Section: Discussionmentioning
confidence: 99%